Protective Effect of Salvia cadmica on Fibroblast Cells from t-bhp-induced Oxidative Damage - Hepokur, Ceylan; Misir, Sema; Cicek, Mehmet; Habtemariam, Solomon; Sharifi-Rad, Javad (Current Pharmaceutical Analysis, 2024)
Background: Salvia species known as
Keywords: CAT